Acute Effects of Resistance Exercise on 24-h Blood Pressure in Middle Aged Overweight and Obese Women - Tibana, R. A.; Pereira, G. B.; Navalta, J. W.; Bottaro, M.; Prestes, J. (International Journal of Sports Medicine, 2013)
This investigation was designed to evaluate responses of blood pressure (BP) following an acute resistance exercise (RE) session. Middle-aged women (N=13) who were classified as overweight (N=8) or obese (N=5) according to body mass index (BMI) participated in the investigation. Participants were randomly submitted to a control session (30-min seated rest) and a exercise session (3 sets, 10 repetitions at 60% 1RM of exercises for the upper and lower body) with systolic (SBP), diastolic (DBP) and mean blood pressure (MBP) obtained at rest and 10, 20, 30, 40, 50, and 60-min following exercise, and through 24 h. Acute RE decreased SBP at 10, 30, and 40-min compared with pre-exercise and control (P<0.05). DBP decreased at 10 and 40-min post-exercise compared with the control trial (P<0.05). Both SBP and DBP decreased in the nighttime period ( − 4.2 mmHg and  − 4.1 mmHg, respectively) and in the overall 24 h period ( − 3.6 mmHg and  − 4.5 mmHg, respectively) following the acute RE session when compared with the control trial. These findings indicate important benefits of acute RE on BP circadian rhythm, particularly at night as well as in the morning, which are critical periods associated with increased risk for cardiovascular events.
Keywords: resistance exercise; hypotension; overweight; cardiovascular events